Icelandic Farmhouses Identity, landscape and construction (1790-1945) - NANNINI, SOFIA (Ricerche. Architettura, Pianificazione, Paesaggio, Design, 2023)
Icelandic Farmhouses. Identity, Landscape and Construction (1790-1945) retraces the history of Icelandic rural architecture between the late eighteenth century and the mid-twentieth century. Through the study of Icelandic rural buildings, this book narrates a very special history of architecture: one of adaptation and tradition, scarcity of building materials and transfers of knowledge with Europe. The history of Icelandic farmhouses is intermixed with construction issues, nationalistic debates, and a quest for a much-needed modernization of the standards of living. The book aims to retrace the role of modern building techniques in the development of Icelandic rural architecture and society.